Envelhecimento humano : estudo sobre a inserção desta temática dentro dos cursos de Psicologia - Longo, Patrícia Di Francesco (2012)
The object of this dissertation was to analyze the spaces occupied by content related to human aging and old age in three higher education institutions located in the northern region of Rio Grande do Sul, specifically in Psychology courses. Studies on human aging and old age become increasingly relevant since population indicators worldwide and national projects an irreversible growth of the elderly population in detriment of relating children and youth. In Brazil, there is a significant reduction in participation in the population aged up to 25 years and the increasing number of elderly. However, it is belived that Psychology courses do not invest in the area of human aging and does not encourage future psychologists to better understand aging. Thus, the need to understand how and how often the content relating to this subject are covered in these courses. In search of answers a qualitative research was conducted, since it enables researchers to work with a vast universe of meanings, reasons, beliefs and values, thus allowing one find answers to very specific questions. Data collection was conducted through semi-structured interviews, focused on understanding the space occupied by the theme in the courses surveyed, performed first with courses coordinators and later with teachers indicated by the coordination. Thus, the sample was chosen for convenience, considering the relevance of these educational institutions at regional level. The data analysis covered the following phases: pre-analysis, material exploration, processing of data and interpretation of content. The foundings showed that aging and old age are subjects scantly covered in Psychology courses and, when they are, the predominant prospect relates the theme directly to illness, to the institutionalization of the elderly and the discipline of human development.